The influence of human settlement on the distribution and diversity of iron-oxidizing bacteria belonging to the Gallionellaceae in tropical streams - Reis, Mariana P.; Ávila, Marcelo P.; Costa, Patrícia S.; Barbosa, Francisco A. R.; Laanbroek, Hendrikus J.; Chartone-Souza, Edmar; Nascimento, Andréa M. A. (Frontiers in Microbiology, 2014)
Among the neutrophilic iron-oxidizing bacteria (FeOB), Gallionella is one of the most abundant genera in freshwater environments. By applying qPCR and DGGE based on 16S rRNA gene-directed primers targeting Gallionellaceae, we delineated the composition and abundance of the Gallionellaceae-related FeOB community in streams differentially affected by metal mining, and explored the relationships between these community characteristics and environmental variables. The sampling design included streams historically impacted by mining activity and a non-impacted stream. The sediment and water samples harbored a distinct community represented by Gallionella, Sideroxydans, and Thiobacillus species. Sequences affiliated with Gallionella were exclusively observed in sediments impacted by mining activities, suggesting an adaptation of this genus to these environments. In contrast, Sideroxydans-related sequences were found in all sediments including the mining impacted locations. The highest and lowest relative frequencies of Gallionellaceae-related FeOB were associated with the lowest and highest concentrations of Fe, respectively. The data enclosed here clearly show distinct species-specific ecological niches, with Gallionella species dominating in sediments impacted by anthropogenic activities over Sideroxydans species.